Evaluation of sustainable, blended learning workforce education for suicide prevention in youth services. (May 2023) - Donovan, Sarah; Maggiulli, Laura; Aiello, Joan; Centeno, Pedro; John, Sydney; Pisani, Anthony
Highlights: InPlace® Learning is a feasible and acceptable approach to suicide prevention education for youth services workers in a large and varied workforce. InPlace® Learning participants demonstrated knowledge and increased self-efficacy in suicide prevention skills. Perception of training relevance and potential for transfer to practice was strong across human services roles and settings. Leveraging implementation science frameworks and strategies strengthened the workforce education suicide prevention initiative. Abstract: Suicide is the second leading cause of death for youth in the U.S. and equipping clinical and non-clinical staff in youth services to address suicide concerns is a challenge. This paper evaluates InPlace Learning, an innovative and sustainable blended learning approach to suicide prevention workforce education in youth services. InPlace Learning combines group video-guided workshops, follow-up Q&A via web-based 'office hours', and continual learning through job aids and brief refreshers. Hillside identified 25 programs to adopt InPlace Learning for suicide prevention training, and 1, 162 staff to participate in the training. The purpose of the first phase of this program evaluation was to evaluate the feasibility of this approach, including examining adoption and reach of InPlace Learning, as well as education outcomes for staff, including knowledge, self-efficacy, and transfer of learning. The program evaluation sample consisted of 556 staff who completed post-training evaluations. Ten staff shared their experience and feedback through post-training interviews. Results show that 100 % (N = 25) of programs adopted InPlace Learning and 64 % of staff participated in the training, showing evidence of reach. Post-training evaluations indicated participants learned skills in suicide prevention. Self-efficacy in connecting around and assessing and responding to suicide concerns rose significantly for both clinical and non-clinical staff. Non-clinical staff who had lower ratings for self-efficacy before training showed the greatest gains post-training. The perception of transfer of learning to practice was high. Staff interview data aligned with quantitative findings. Taken together, these findings indicate that InPlace Learning is a feasible and acceptable approach to suicide prevention workforce education in youth services with a positive impact on educational outcomes for staff.